Students’ attitudes on personal drug selection exercise in writing prescription - Kumar, Manish; Mohan, Lalit; Mishra, Hitesh; Chandra, Akash; Dikshit, Harihar (International Journal of Basic & Clinical Pharmacology, 2017)
Background: This study was developed to know the students’ views regarding personal drug (P-drug) concept in rational prescription of drugs and also giving them training of creating and using personal drug concept. Methods: 40 medical students (5th semester) divided in four groups were involved voluntarily in a three phase, questionnaire based and prospective study. In first and second phase students were taught and asked to derive P-drug using different standard text books and Current Index of Medical Specialties (CIMS) by analyzing efficacy, safety, cost and convenience of drugs used for type II diabetes mellitus. Third phase was designed to know the students’ perception regarding the exercise and difficulties faced in the process of P-drug selection. It contained demographic and 12 questions with answer using Likert scale. Results: Students selected biguanide (metformin) as a P-drug in terms of efficacy, safety, cost and convenience. 95% (36 out of 40) responded in the questionnaire, out of which 92% (33 out of 36) had given answer with mean score ≥4. Overall median score was 4 and Interquartile Range was 4-5. 89% (32) strongly agreed that P-dug selection teaching helped them to understand pharmacology better. Majority (83% or 30) were in favour of introducing P-drug selection exercises in undergraduate pharmacology curriculum. Conclusions: P-drug selection exercise helped students to understand the differences among various drugs used for the treatment of type II diabetes mellitus and given them a strong foundation for developing rational use of the medicine in their future career as a doctor.